2019
DOI: 10.1016/j.celrep.2019.01.084
|View full text |Cite
|
Sign up to set email alerts
|

MAP7D2 Localizes to the Proximal Axon and Locally Promotes Kinesin-1-Mediated Cargo Transport into the Axon

Abstract: Summary The motor protein kinesin-1 plays an important role in polarized sorting of transport vesicles to the axon. However, the mechanism by which the axonal entry of kinesin-1-dependent cargo transport is regulated remains unclear. Microtubule-associated protein MAP7 (ensconsin in Drosophila ) is an essential kinesin-1 cofactor and promotes kinesin-1 recruitment to microtubules. Here, we found that MAP7 family member MAP7D2 concentrates at the proximal axon, where it overlap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 34 publications
4
53
0
Order By: Relevance
“…The underlying mechanisms of kinesin-1 selectivity are complex, and might involve the ability of the motor to regulate the properties of the tracks on which it walks (Shima et al, 2018). Importantly, KIF5B shows a very strong dependence on MAP7 family members, which control both kinesin recruitment to the MT and its activation (Hooikaas et al, 2019;Metzger et al, 2012;Monroy et al, 2018;Pan et al, 2019). MAP7 and its homologues are more abundant on older MTs, apparently because of their slow association with growing MTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanisms of kinesin-1 selectivity are complex, and might involve the ability of the motor to regulate the properties of the tracks on which it walks (Shima et al, 2018). Importantly, KIF5B shows a very strong dependence on MAP7 family members, which control both kinesin recruitment to the MT and its activation (Hooikaas et al, 2019;Metzger et al, 2012;Monroy et al, 2018;Pan et al, 2019). MAP7 and its homologues are more abundant on older MTs, apparently because of their slow association with growing MTs.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we set out to investigate the spatial regulation of the activity of the kinesins associated with Rab6 vesicles. Previous work has shown that KIF5B depends on the members of MAP7 family for its activation (Hooikaas et al, 2019;Metzger et al, 2012;Monroy et al, 2018;Pan et al, 2019), while kinesin-3 is inhibited by MAP7 (Monroy et al, 2018;Monroy et al, 2020).…”
Section: Combination Of Kif5b and Kif13b Allows Rab6 Vesicles To Reacmentioning
confidence: 98%
See 1 more Smart Citation
“…MAP7 on the other hand facilitates the binding of kinesin-1 to MTs via its interaction with the stalk domain (Monroy et al, 2018 ; Hooikaas et al, 2019 ). Said interaction was recently shown to be important for axonal sorting of cargoes, as MAP7D2 isoform preferentially localizes to MTs in the proximal axon region, where it recruits kinesin-1 (Pan et al, 2019 ).…”
Section: Molecular Drivers Of Anterograde Axonal Transport and Their mentioning
confidence: 99%
“…Thus, this unique microtubule binding property of MAP7, likely mediated by peptides outside the N domain, provides a novel mechanism to regulate microtubule stability in neurons. As recent work (Hooikaas et al, 2019;Pan et al, 2019) reported diverse functions of mammalian MAP7 homologs, it would thus be interesting to determine whether these homologs have similar microtubule binding properties as MAP7.…”
Section: Map7 Promotes Stable Microtubules In Mature and Nascent Branmentioning
confidence: 99%